2014
DOI: 10.1159/000362153
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Nicotine Exposure Exacerbates Neonatal Hyperoxia-Induced Lung Fibrosis in Rats

Abstract: Background: Maternal nicotine exposure increases lung collagen in fetal and newborn animals. Connective tissue growth factor (CTGF) plays a role in hyperoxia-induced pulmonary fibrosis. Objective: To determine whether pre- and postnatal nicotine exposure can augment CTGF expression and postnatal hyperoxia-induced lung fibrosis. Methods: Nicotine was administered to pregnant Sprague-Dawley rats at a dose of 6 mg/kg/day from gestational days 7-21 (prenatal nicotine-treated group) and gestational day 7 to postnat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 20 publications
3
15
0
Order By: Relevance
“…Myofibroblasts are differentiated fibroblasts that possess contractile properties similar to those of smooth muscle cells, and they are characterized by the presence of α-SMA. EMT has been categorized based on the physiological context into 3 distinct types: developmental, fibrosis and wound healing, and cancer [12]. Epithelial cells express high E-cadherin levels, whereas mesenchymal cells express high N-cadherin and FSP-1 levels [24].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Myofibroblasts are differentiated fibroblasts that possess contractile properties similar to those of smooth muscle cells, and they are characterized by the presence of α-SMA. EMT has been categorized based on the physiological context into 3 distinct types: developmental, fibrosis and wound healing, and cancer [12]. Epithelial cells express high E-cadherin levels, whereas mesenchymal cells express high N-cadherin and FSP-1 levels [24].…”
Section: Discussionmentioning
confidence: 99%
“…There exists a vast amount of literature describing the mechanisms of smoking- and nicotine-induced lung fibrosis [10,11]. We recently demonstrated that maternal nicotine exposure induces lung injuries and fibrosis, which is shown by increased inflammatory cell recruitment and collagen synthesis in the lungs of rat offspring [12]. Epithelial-mesenchymal transition (EMT) following lung injury is a process in which epithelial cells lose their cell polarity and cell-cell adhesion features and gain migratory properties to become mesenchymal (fibroblast-like) cells [13].…”
Section: Introductionmentioning
confidence: 99%
“…The kidney tissues used for these experiments were obtained from a previous study designed to assess lung fibrosis (36). All rats described in the present manuscript were kept at room air and were not exposed to 95%/60% O 2 .…”
Section: Animalsmentioning
confidence: 99%
“…Neonatal hyperoxia-induced lung injury serves as an excellent model for mechanistic studies to better understand how hyperoxia disrupts lung development and for preclinical testing of potential therapies for BPD. “Two hit” models have combined postnatal hyperoxia with antenatal lipopolysaccharide (LPS) to represent perinatal inflammation, such as chorioamnionitis [34, 35]; hyperoxia and maternal nicotine administration [36] and hyperoxia with intermittent hypoxia to represent combined injuries [37-39] in the pathogenesis of experimental BPD.…”
Section: Introductionmentioning
confidence: 99%